Reincarnation in Tibetan Buddhism - Simonds, Colin H. (Canadian Journal of Buddhist Studies, 2020)
RUTH GAMBLE, Reincarnation in Tibetan Buddhism: The Third Kar-mapa and the Invention of a Tradition. New York, NY: Oxford Uni-versity Press, 2018. XVI, 322 pp. CAN $108.99 (hb). ISBN 978-0-19-069077-9,